Sustainability assessment of BRAC's rural development programme: a pilot study - Rafi, Mohammad; Akther, Shahnuj (Research and Evaluation Division, Brac, 2019)
This is a pilot study on the sustainability of BRAC Rural Development Prgoramme (RDP). As because of the short duration (I) the sustainability of social and economic aspects of RDP VOs and (2) the sustainability of AO at organizational, human resource, and financial levels have been taken into consideration in this study. In 1998 a sustainability work plan (SWP) was developed for BRAC. By using it the study has operationalized the plan. The sustainability assessment has been done in tenns of four levels that the VOs were expected to pass through, i.e., Level l: 13-36 months old, Level 2: 37-48 months old, Level 3: 49-72 months old, and Level 4: 73-96 months old. Data for the study were derived from three sources. First, a survey was conducted for this study. Three AOs for each level, three VOs from each AO, and nine members from each VOs have been randomly selected and surveyed. Thus, the survey observed 12 AOs, 36 VOs, and 324 YO members. Second, data collected for studies conducted in the past were reanalyzed and used to support the objectives of this study. Third, data on finances were derived from RDP's Management Information System (MIS) and Accounts Department. The VOs were expected to evolve over a period, as they mature they get a step closer in meeting their objectives. It was assun1ed that the VOs at each level would cumulate the attributes reflecting sustainability present in the preceding levels. The levels considered were based on the shift in two VO characteristics. First, shift from BRAC dependent management to selfmanagement. Second, from a BRAC related credit channeled through a development action to a fully autonomous civic body. Although the complete machinery (committees) as framed by BRAC for self-management were not present in all VOs it appeared that they achieved some capacity in managing themselves. The members both collectively and individually projected organizational capacities and powers both at social and economic aspects. Similarly they projected a higher capacity to take decision and conduct activities of their own particularly those relating to credit. Of course in many instances they took advice of BRAC for action. As a whole the members both individually and collectively showed a higher level of perfonnance in all the aspects of sustainability. It was highest in the case of both social and economic wellbeing but a little less in the case of social organizational capacity. The study intends to show different stages that VOs pass through over a period. The directions in which things are moving, not what they are at any given time are important. The achievement of sustainability was expected to project a trend over a period. Although the VOs and AOs projected a satisfactory level of sustainability but failed to show a trend that it increased with their aging. In the case of most indicators the younger and older VOs projected a higher level of sustainability. The findings indicate that the sustainability did not cumulate over time. The absence of a visible sustainability trend was probably because of the fact that the study was conducted on a small sample not representative ofBRAC VOs. Therefore the findings over here should not be considered conclusively. The model used in this study was observed to be effective in the sustainability assessment of RDP. The Research and Evaluation Division plans to keep on contributing to the SWP by assessing the sustainability of different components of BRAC. As a first step to this, the sustainability of AOs and VOs with a special attention to the I GAs of VO members and with a larger coverage so that the findings may be representative of the entire program will be assessed shortly.